2009
DOI: 10.1002/adsc.200800608
|View full text |Cite
|
Sign up to set email alerts
|

The Ion Tag Strategy as a Route to Highly Efficient Organocatalysts for the Direct Asymmetric Aldol Reaction

Abstract: Abstract:The installation of an imidazolium tag via acetate connection to the C-4 of cis-4-hydroxy-lproline provides a highly efficient catalyst for the direct asymmetric aldol reaction, that works in a remarkably low catalyst loading (0.1 mol%) affording TONs up to 930 in the case of electron-poor aromatic aldehydes with ee up to > 99%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(38 citation statements)
references
References 76 publications
0
35
0
1
Order By: Relevance
“…They found that catalyst loading could be reduced to 0.1 mol% in the case of electron-poor aromatic aldehydes with ee up to 99%. Under the same reaction conditions, many substrates afforded "enzymatic-like" levels of ees [60]. The recyclability of the catalyst was examined and shown that the product could be readily isolated by extraction using diethyl ether after the excess ketone was removed by vacuum.…”
Section: Scheme 3 Aldol Reaction Catalyzed By An Imidazolium-tagged mentioning
confidence: 99%
“…They found that catalyst loading could be reduced to 0.1 mol% in the case of electron-poor aromatic aldehydes with ee up to 99%. Under the same reaction conditions, many substrates afforded "enzymatic-like" levels of ees [60]. The recyclability of the catalyst was examined and shown that the product could be readily isolated by extraction using diethyl ether after the excess ketone was removed by vacuum.…”
Section: Scheme 3 Aldol Reaction Catalyzed By An Imidazolium-tagged mentioning
confidence: 99%
“…However, lower yields were achieved using aliphatic aldehydes as electrophiles (52-60%), but still excellent diastereo-and enantioselectivities (99% de, 99% ee). Under these conditions, the catalyst was recovered and reused up to five times without deleterious effect in the results [105,106]. Figure 11.…”
Section: Aqueous Aldol Reactions With Supported Organocatalystsmentioning
confidence: 99%
“…Lombardo 小组 [69,70] 离子对有利于提高催化反应的立体选择性. 因此设计、 合成了带离子对的吡咯衍生物 25 (Scheme 9), 催化脂肪 醛(正丙醛、正丁醛、正戊醛、异戊醛和异丁醛)与各种 取代的硝基乙烯的 Michael 加成放应 [71] .…”
unclassified